1979
DOI: 10.1149/1.2129060
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Film Formation on Cobalt‐Hardened Gold

Abstract: Cobalt‐hardened gold electrodeposits have been thermally oxidized under dry oxidation conditions in the temperature range 150°–250°C. Auger depth profiling and ESCA are employed to characterize the surface films as a function of time and temperature. Below 175°C, only normalCoO is observed, as confirmed by ESCA. Above 175°C, normalCoO growth is observed to decrease substantially and is qualitatively related to the recrystallization phenomena of the gold deposit. In this same temperature range, potassium ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The codeposition of an insulating film from cobalt-or nickel-hardened acid gold baths has caused significant problems for electrical contacts. High electrical resistivity can be observed upon thermal aging (e.g., 150 C), especially in films plated at high speeds with high cobalt concentration [26]. The subject has received considerable attention since the late 1960s when high contact resistance on telephone spring contacts was correlated with an orange-brown film on gold-plated contacts.…”
Section: Acid Cyanide Bathsmentioning
confidence: 99%
“…The codeposition of an insulating film from cobalt-or nickel-hardened acid gold baths has caused significant problems for electrical contacts. High electrical resistivity can be observed upon thermal aging (e.g., 150 C), especially in films plated at high speeds with high cobalt concentration [26]. The subject has received considerable attention since the late 1960s when high contact resistance on telephone spring contacts was correlated with an orange-brown film on gold-plated contacts.…”
Section: Acid Cyanide Bathsmentioning
confidence: 99%
“…ening agent such as a cobalt salt. Recently, it was found that the inclusion of cobalt in the gold at concentrations above a certain limit may cause the formation of a highly resistive, cobalt-containing surface film (COO) when the gold is aged at moderately high temperatures (,--150~ (1). As a practical solution to this…”
mentioning
confidence: 99%
“…This phenomenon occurs especially severely when the metallic cobalt content of the gold is high, because the increased contact resistance is a result of the formation of CoO on the surface, which is produced upon thermal oxidation of metallic Co, and not by the Co-CN complex included in the gold (52,53).…”
Section: (I) Electrical Contact Resistancementioning
confidence: 99%